Generation of physical map contig-specific sequences - Jiang, Yanliang; Xu, Peng; Liu, Zhanjiang (Frontiers in Genetics, 2014)
Rapid advances of the next-generation sequencing technologies have allowed whole genome sequencing of many species. However, with the current sequencing technologies, the whole genome sequence assemblies often fall in short in one of the four quality measurements: accuracy, contiguity, connectivity, and completeness. In particular, small-sized contigs and scaffolds limit the applicability of whole genome sequences for genetic analysis. To enhance the quality of whole genome sequence assemblies, particularly the scaffolding capabilities, additional genomic resources are required. Among these, sequences derived from known physical locations offer great powers for scaffolding. In this mini-review, we will describe the principles, procedures and applications of physical-map-derived sequences, with the focus on physical map contig-specific sequences.